The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1993
DOI: 10.1111/j.1365-2311.1993.tb01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme adaptive life‐cycle in a high arctic aphid,Acyrthosiphon svalbardicum

Abstract: 1. The year-round biology of a high arctic aphid is described for the first time.2. The life-cycle is shown to be genetically determined, and thus markedly different to temperate species where the observed polymorphism is governed primarily by external environmental cues.3. The fundatrix, which emerges from the overwintering egg, gives birth directly to sexual morphs, a phenomenon previously undescribed in the Aphidinae. This process is essentially prevented in temperate aphids by an endogenous mechanism, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 23 publications
(15 reference statements)
1
35
0
Order By: Relevance
“…On the other hand, it has also been reported that stem mothers produce sexual morphs under very short days in Drepanosiphum platanoides and Eucallipterus tiliae in Scotland (Dixon, 1972(Dixon, , 1971. Stem mothers of Acyrthosiphon brevicorne and Acyrthosiphon svalbardicum living in high arctic regions, where the season for growth and reproduction is shorter than in temperate regions, produce sexual morphs in natural conditions (Strathdee et al, 1993;Strathdee and Bale, 1996). Thus, the strength and duration of the seasonal timer should be adaptive to local climates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has also been reported that stem mothers produce sexual morphs under very short days in Drepanosiphum platanoides and Eucallipterus tiliae in Scotland (Dixon, 1972(Dixon, , 1971. Stem mothers of Acyrthosiphon brevicorne and Acyrthosiphon svalbardicum living in high arctic regions, where the season for growth and reproduction is shorter than in temperate regions, produce sexual morphs in natural conditions (Strathdee et al, 1993;Strathdee and Bale, 1996). Thus, the strength and duration of the seasonal timer should be adaptive to local climates.…”
Section: Discussionmentioning
confidence: 99%
“…These low SCP values were linked to long-term cold hardiness in which 80% of eggs survived for a month at -30°C (Strathdee et al, 1995). The life cycle of A. svalbardicum is genetically programmed (unlike temperate aphids) with a minimum of two generations (fundatrix and the sexual morphs, ovipara and male) and a maximum of three generations, in which the fundatrix produces some viviparae (in addition to the males and oviparae) and these give rise to a third generation consisting exclusively of the two sexual morphs (Strathdee et al, 1993b). Developmental analyses found that 470 day-degrees above a threshold of 0°C were required to complete the two generation egg r fundatrix r sexual morphs r egg life cycle whereas 710 day-degrees were required for the egg r fundatrix r vivipara r sexual morphs r egg route (Strathdee et al, 1993a).…”
Section: Impacts Of Climate Warming On Insect Overwinteringmentioning
confidence: 99%
“…2, 4). Sex ratios, measured as the proportion of males to winged females (Ward and Wellings 1994), were usually less than 1: 1, and lowest (<0.35: 1) for Me2 (Table 1). Me2 produced less than 20% males at any photoperiod, compared with 30-40% for the other clones ( Fig.…”
Section: Resultsmentioning
confidence: 99%